2006
DOI: 10.1002/app.23093
|View full text |Cite
|
Sign up to set email alerts
|

Thermoplastic apparent interpenetrating polymer networks of polyurethane and styrene/acrylic acid block copolymer: Structure–property relationships

Abstract: Thermoplastic apparent interpenetrating polymer networks (t-AIPNs) of crystallizable polyurethane (CPU) and a styrene/acrylic acid block copolymer (S-b-AA, acid form) of several compositions were prepared by casting from a common solvent. A variety of experimental techniques, including size exclusion chromatography (SEC), differential scanning calorimetry (DSC), thermogravimetric analysis (TGA), dynamic mechanical analysis (DMA), broadband dielectric relaxation spectroscopy (DRS), thermally stimulated depolari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
0
7
0
1
Order By: Relevance
“…Four peaks are observed in Fig. 7.6, all arising from PU (Kanapitsas et al, 2006): in the order of increasing temperature, the local, secondary g and b relaxations in the glassy state, the cooperative, segmental a relaxation in the region of the glass transition, and the interfacial MWs relaxation in the rubbery state. in previous work the g relaxation has been ascribed to crankshaft motion of methylene sequences with participation of adjacent polar groups and the b relaxation to motions of carbonyl groups with attached water molecules (Kanapitsas et al, 2006).…”
Section: 4mentioning
confidence: 89%
See 4 more Smart Citations
“…Four peaks are observed in Fig. 7.6, all arising from PU (Kanapitsas et al, 2006): in the order of increasing temperature, the local, secondary g and b relaxations in the glassy state, the cooperative, segmental a relaxation in the region of the glass transition, and the interfacial MWs relaxation in the rubbery state. in previous work the g relaxation has been ascribed to crankshaft motion of methylene sequences with participation of adjacent polar groups and the b relaxation to motions of carbonyl groups with attached water molecules (Kanapitsas et al, 2006).…”
Section: 4mentioning
confidence: 89%
“…the systematic study of the MWs peak provides information on microphase separation. More specifically, it has been shown that the difference T MWs -T a increases with increasing degree of microphase separation (DMs) and, thus, T MWs -T a provides a measure for DMs (Kanapitsas et al, 2006). This criterian cannot be, however, rigorously applied here, as additional ions introduced by the clay particles affect conductivity and, thus, the temperature position of the MWs peak.…”
Section: 4mentioning
confidence: 93%
See 3 more Smart Citations